Educational Technology about Palliative Care on Instagram and Youtube (Research, Society and Development, 2021)
Social media is a way to carry out health education actions. to report the use of educational technologies, specifically videos, and brochures, on palliative care on Instagram and YouTube. Thus, this article aims to report the use of innovative technology, carried out between June 2020 and February 2021, by professors and students linked to an extension project. Instagram and YouTube were the settings for the experience. We constructed 24 leaflets and educational videos on palliative care. The themes dealt with clinical, social, economic, and mourning aspects. We published these materials in project profiles. About users, the majority were female, in the age group between 25-34 years. Access to the materials was predominantly through mobile devices. On Instagram, the most viewed theme was the importance of sleep at the end of life and control of dyspnea. As for the leaflets, the ones with the best impressions were those on non-pharmacological pain relief, management of nausea and vomiting, and withdrawal of renal replacement therapies at the end of life. On YouTube, a video with greater reach was about advanced directives. We concluded that Instagram and YouTube are social media with the potential to disseminate educational technologies because they are easily accessible and can be employed by nursing to develop educational actions.